Investigation on adhesion of Sulfobacillus thermosulfidooxidans via atomic force microscopy equipped with mineral probes - Li, Q.; Becker, Thomas; Zhang, R.; Xiao, T.; Sand, W. (Elsevier BV, 2019)
© 2018 Elsevier B.V. Bacterial adhesion is a key step to prevent environmental problems called acid mine drainage or to improve leaching efficiency in industry, since it initiates and enhances bioleaching. Thus, to analyze bacterial adhesion and to understand this process is crucial. In this study atomic force microscopy equipped with a pyrite or chalcopyrite tip was applied to study the adhesion of Sulfobacillus thermosulfidooxidans. The results illustrate that planktonic cells of both pyrite- and sulfur-grown cells of S. thermosulfidooxidans show more affinity to pyrite than to chalcopyrite (adhesion forces 2 nN versus 0.13 nN). However, the interactions between bacteria and chalcopyrite can be strengthened, if the bacteria are brought into contact with the chalcopyrite. The biofilm cells show low affinity to either pyrite or chalcopyrite. A high content of proteins in the extracellular polymeric substances collected from planktonic cells of S. thermosulfidooxidans and a low content of proteins collected from biofilm EPS indicates that proteins play an important role in initial adhesion. Analysis of adhesion force-distance curves reveal that adhesion by pyrite-grown cells is a complex interaction involving several bonding forces.